Klawde : Evil Alien Warlord Cat - Marciano, Johnny; Chenoweth, Emily (Klawde: Evil Alien Warlord Cat, 2019)
Klawde, the exiled ruler of the planet Lyttyrboks, and Raj, who just moved from Brooklyn to tiny Elba, Oregon, forge an unlikely friendship as they find their footing in a strange new world.